2021
DOI: 10.1111/jan.14791
|View full text |Cite
|
Sign up to set email alerts
|

Hidden figures of nursing: The historical contributions of Black nurses and a narrative for those who are unnamed, undocumented and underrepresented

Abstract: Hidden figures of nursing: The historical contributions of Black nurses and a narrative for those who are unnamed, undocumented and underrepresented Unless I am allowed to tell the story of my life in my own way, I cannot tell it at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The medical model, combined with sexism and gender-based roles, has influenced many healthcare organizations' nursing leadership behaviors ( 4 ) . There are also hierarchical issues within our profession and our narrative have privileged the voices of the status quo and in some instances perpetuated structural racism ( 5 ) .…”
Section: Leadership In a New World Ordermentioning
confidence: 99%
“…The medical model, combined with sexism and gender-based roles, has influenced many healthcare organizations' nursing leadership behaviors ( 4 ) . There are also hierarchical issues within our profession and our narrative have privileged the voices of the status quo and in some instances perpetuated structural racism ( 5 ) .…”
Section: Leadership In a New World Ordermentioning
confidence: 99%
“…The following 2 articles address race and nursing from a policy 1 and historical 2 perspective. The policy piece focuses more on nurses in perinatal care, 1 whereas the historical piece paints a short, sweeping picture of Black nurses in the diaspora 2 …”
Section: Race and The Nursing Workforcementioning
confidence: 99%
“…This piece provides a brief overview of Black women in nursing and, perhaps more importantly, a reference list for those interested in reading more about the contributions of Black women in the diaspora to nursing and to healing more broadly 2 . Mary Jane Seacole, a contemporary of Florence Nightingale who served in the Crimea and left an account of her life, starts the article.…”
Section: Race and The Nursing Workforcementioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the work continues, and every citizen, profession, and institution have a role in assisting the country to emerge from its worst moments to a more robust, freer, and more just Nation, including the nursing profession. From my perspective as an African American nurse and an urban university faculty member, a literature review on racism in nursing revealed parallel information about nations' legacies of structural racism and inequities in nursing 3–6. One would like to think otherwise, but evidence suggests the legacy of racial inequities in the United States has influenced the development of the nursing profession.…”
mentioning
confidence: 99%